Care for Cardiac Arrest on Golf Courses: Still Not up to Par?. (1st January 2015) - Deutsch, Leisa; Paternoster, Ryan; Putman, Kevin; Fales, William; Swor, Robert
Abstract Introduction. Early CPR and use of automated external defibrillators (AEDs) have been shown to improve cardiac arrest (CA) outcomes. Placement of AEDs on golf courses has been advocated for more than a decade, with many trade golf publications calling for their use. Objective. To describe the incidence and treatment of CAs at Michigan golf courses and assess the response readiness of their staff. Methods. We performed a retrospective study of CA on Michigan golf courses from 2010 to 2012. Cases were identified from the Michigan EMS Information (MI-EMSIS) database. Cases with "golf" or "country club" were manually reviewed and location type was confirmed using Google Maps. We conducted a structured telephone survey capturing demographics, course preparedness, including CPR training and AED placement, and a description of events, including whether CPR was performed and if an AED was used. Our primary area of interest was the process of care. We also recorded return of spontaneous circulation (ROSC) as an outcome measure. EMS Utstein data were collected from MI-EMSIS. Descriptive data are presented. Results. During the study period, there were 14, 666 CAs, of which 40 (0.18%) occurred on 39 golf courses (1 arrest/64 courses/year). Of these, 38 occurred between May and October, yielding a rate of 1 arrest/33.5 courses/golf season. Almost all (96.2%) patients were male, mean age 66.3 (range 45–85), 68% had VT/VF, and 7 arrested after EMS arrival. Mean interval from 9-1-1 call to EMS arrival at the patient was 9:45 minutes (range 3–20). Of all cases, 24 (72.3%) patients received CPR with 2 patients having CPR performed by course staff. Although AEDs were available at 9 (22.5%) courses, they were only placed on 2 patients prior to EMS arrival. Sustained ROSC was obtained in 12 (30.0%) patients. Only 7, (17.9%) courses required CPR/AED training of staff. Conclusion. When seasonally adjusted, the rate of cardiac arrest on Michigan golf courses is similar to that of other public locations. AED use was rare even when available. Preparedness for and response during a CA is suboptimal. Despite more than a decade of advocacy, response to golf course cardiac arrest is still not up to par.